EFL Teachers’ and Students’ Perceptions about Communication Strategies Teachability - Raziyeh Behroozian; Nasser Ghafoori; Saeideh Ahangari (Journal of English Language Pedagogy and Practice, 2021)
The current study examined the Iranian EFL teachers’ and students’ perceptions about Communication Strategies Teachability. The study was conducted with 20 teachers and 110 students from universities and private language Institutes in Tabriz, Iran. The literature regarding the teachability of communication strategies (CSs) has been far from conclusive. Some researchers reject the possibility of CSs instruction while many empirical studies support their teachability. Taking a mixed method design, the present study used a language proficiency test, a questionnaire and an interview for data collection. In the quantitative phase, the participants’ responses to questionnaire before and after a 12-week period of teaching CSs were statistically compared. The analysis of the quantitative data obtained from the questionnaire through Paired-samples t-test indicated that the students’ perceptions towards the usefulness of CSs grew significantly more positive after their instruction. The qualitative analysis of the interview data collected from the teachers indicated that most teachers found CSs useful and possible to teach. It was also found that these strategies improved capability of English language learners to speak and enhaned their conciousness of CSs. This study could offer pedagogical implications for both teachers and students and pave the way for further studies in the field.